Implementasi Metode Promethee Dalam Sistem Pendukung Keputusan Penilaian Raport Dosen - Dyah Apriliani; Oman Somantri (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
Assessment of lecturer report cards is a decision-making process using information obtained through measuring the results of lecturer performance by students and administrative completeness of each lecturer. The object used in this study is the Informatics Engineering IV Study Program using the promethee method. The Promethee method is used to obtain a ranking of grades from lecturers. Promethee's method of calculating requires several alternatives and criteria. The alternative used for assessment is the lecturer who teaches in the D IV Informatics Engineering Study Program. The criteria used to assess each alternative are lecturer assessment data by students which includes student assessment input taken from the final score or the average resulting from the questionnaire assessment filled in by students. Administrative appraisal data which includes: syllabus collection, collection of college contracts, modules, number of attendance, timeliness of UTS and UAS collection questions as well as the timeliness of collecting UTS and UAS scores. From this study, the assessment of lecturer report cards was obtained, which also included lecturer rankings based on the scores produced. System testing is done by comparing the results of manual assessment with the results of the assessment produced by the system. Based on the testing that has been done it can be concluded that the results of testing both manually and using the system are the same.